2016
DOI: 10.3389/fpsyg.2016.01525
|View full text |Cite
|
Sign up to set email alerts
|

Changing Conspiracy Beliefs through Rationality and Ridiculing

Abstract: Conspiracy theory (CT) beliefs can be harmful. How is it possible to reduce them effectively? Three reduction strategies were tested in an online experiment using general and well-known CT beliefs on a comprehensive randomly assigned Hungarian sample (N = 813): exposing rational counter CT arguments, ridiculing those who hold CT beliefs, and empathizing with the targets of CT beliefs. Several relevant individual differences were measured. Rational and ridiculing arguments were effective in reducing CT, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 31 publications
4
92
2
1
Order By: Relevance
“…Our contribution shows that people consider conspiracy theories as a social cost. As it turns out that ridiculing arguments of those who believe in conspiracy theories is effective to reduce belief in conspiracy theories (Orosz et al., ), the challenge is to ensure, at the same time, that we avoid contributing to this stigma. Hence, interventions aimed at addressing this important societal phenomenon should take into account this aspect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our contribution shows that people consider conspiracy theories as a social cost. As it turns out that ridiculing arguments of those who believe in conspiracy theories is effective to reduce belief in conspiracy theories (Orosz et al., ), the challenge is to ensure, at the same time, that we avoid contributing to this stigma. Hence, interventions aimed at addressing this important societal phenomenon should take into account this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being qualified as possessing such flaws, conspiracy believers are often considered in the collective imagination as suffering from mental health disorders, such as paranoia (Bratich, ; Harambam & Aupers, , ; Husting & Orr, ; Sparkman, ). Moreover, ridiculing arguments of those who believe in conspiracy theories has been found to be an effective lever to reduce belief in conspiracy theories (Orosz et al., ). In sum, social views of conspiracy (e.g., theories, beliefs, believers, etc.)…”
Section: The Hypothesis Of Conspiracy Theories As a Social Stigmamentioning
confidence: 99%
“…Jolley and Douglas () showed that presenting counterconspiracy information before conspiracy information—in other words “inoculating” people against conspiracy theories—can reduce belief. Orosz, Krekó, Paskuj, Tóth‐Király, Bothe, and Roland‐Lévy () showed that counterarguing and even ridiculing conspiracy claims could be effective in reducing conspiracy belief. In future efforts, researchers may consider some of the techniques used to address misinformation more generally (e.g., counterarguing, retraction, prewarning; see Flynn et al, for an overview).…”
Section: Definitionsmentioning
confidence: 99%
“…The study additionally incorporated self-reflectiveness (i.e., willingness to acknowledge the possibility of being incorrect). Researchers have not previously examined this in relation to belief in conspiracies [43], however believers in conspiracy theories typically resist alternative arguments, particularly of a rational nature [45]. Self-certainty and self-reflectiveness represent facets of cognitive insight, which can be conceptualised as the mental processes involved in self re-evaluation of anomalous experiences and misunderstandings [46][47]).…”
Section: The Present Researchmentioning
confidence: 99%